PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) UNTUK MENINGKATKAN HASIL BELAJAR IPA KELAS VC SD NEGERI 010 PASIR PUTIH KECAMATAN BATANG GANSAL KABUPATEN INDRAGIRI HULU - Guntoro Guntoro; Damanhuri Daud; Jesi Alexander Alim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrac: The purpose of this research to improve the resultof learning IPA students class Vc SD Negeri 010 Pasir putih of academic year 2014/2015. The subject of the research is students class Vc SD Negeri 010 Pasir putih consist of 27 students, 13 male students, and 14 female students. The type of the research is classroomaction research (PTK) with two cycles. The data collection show that the result of learning student obtain increased, the score of teachers, activity 73,60%. Cycle II mounting horizontally- flaten 87,09%. Sudent activity in cycles I bay average is 68,05% in,in cycles II increasingly byaverage is 81,94%. The data of the result research obtain increased,that before doing action Group Investigation (GI) model in basic score 10 people (37,03%) by average of score 64,59%. in cycles I incrased by complete achieve 13 people (48,14%) by average of score 68,51%. In cycles II increase by complete achieve 23 people (85,18%), by average of score 81,77. So that the increasingly of the result learning by 26,59%. The conculusion of the hypotesis in this reseach is “ if the implemented learning model Group Investigation (GI) So it can be increased the result of learnig IPA students class Vc SD Negeri 010 Pasir putih can” be acceept.Keywords : Cooperative Learning Model Type Group Investigation (GI) The Result Of Learning IPA.